Language Works 7(1) - Andersen, Elisabeth Muth; Dalberg, Line; Rasmussen, Sidsel; Schöps, Antje; Nicolaisen, Emilie Munch; Thorsen, William Miki; Thøgersen, Jacob (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2022)
Welcome to the 12th issue of Language Works. After two years (has it really ”only” been two years?) in the shadow of Covid, we are now back to studies and research as we know it. This also means a new issue of Language Works, which this time around is bursting at the seams with a total of five articles that span across the broad field of linguistics. Welcome, and happy reading!